Феноменологія як трансцендентальна теорія політичного світу - Ґняздовський, А. (Інститут філософії ім. Г.С. Сковороди НАН України, 2009)
The main problem of the paper is to what extent the political can become a subject of phenomenology as a transcendental philosophy. Its starting point is Ludwig Landgrebe's thesis that if phenomenology is to be a transcendental philosophy, it is — consistently thought out to an end — a transcendental theory of history. Referring to this thesis, the author poses the question: would the meaning of phenomenological transcendentalism not be consistently thought out to an end only if phenomenology proved its capacity as a transcendental theory of the political? In order to answer this critical question Landgrebe's thesis is interpreted from the perspective of Klaus Held's project of a «phenomenology of the political world». The author of this paper analyses the categorial relationship between both projects and poses two questions in this context: To what extent the problem of the political falls within the scope of phenomenology as a transcendental theory of history and how far the phenomenology of the political world can be understood as a transcendental theory of the political.